White and null votes in Brazilian presidential elections: period between 2002 and 2018 - da Silva Valente, Maria Rita (2022)
The present study aims to analyze the behavior of invalid voting (blank and null) in the brazilian presidential elections from 2002 to 2018, seeking to assess if there is a correlation between invalid votes and the Brazilian States Human Development Index. The main hypothesis of this work is that the significant negative correlation between these variables found by other authors with respect to the elections in the years 1989-2002 has changed in the last twenty years: increasingly, there is no significance in the joint behavior of invalid votes and HDI. We corroborate this hypothesis by means of an analysis of the contemporary political and electoral environment for each of the five elections from 2002 to 2018 and an updated statistical calculus of the correlation (Pearson’s coefficient) of the two relevant variables. This work concludes with a survey of explanatory conjectures, admittedly of an exploratory nature, about the fact that the correlation between HDI and invalid votes has become statistically insignificant.